Normothermic Regional Perfusion in Pediatric Controlled Donation After Circulatory Death Can Lead to Optimal Organ Utilization and Posttransplant Outcomes. Issue 3 (12th October 2022) - Miñambres, Eduardo; Estébanez, Belen; Ballesteros, Maria Ángeles; Coll, Elisabeth; Flores-Cabeza, Eva Mercedes; Mosteiro, Fernando; Lara, Ramón; Domínguez-Gil, Beatriz
Abstract : Background: The benefits of normothermic regional perfusion (NRP) in posttransplant outcomes after controlled donation after the determination of death by circulatory criteria (cDCD) has been shown in different international adult experiences. However, there is no information on the use of NRP in pediatric cDCD donors. Methods: This is a multicenter, retrospective, observational cohort study describing the pediatric (<18 y) cDCD procedures performed in Spain, using either abdominal NRP or thoracoabdominal NRP and the outcomes of recipients of the obtained organs. Results: Thirteen pediatric cDCD donors (age range, 2–17 y) subject to abdominal NRP or thoracoabdominal NRP were included. A total of 46 grafts (24 kidneys, 11 livers, 8 lungs, 2 hearts, and 1 pancreas) were finally transplanted (3.5 grafts per donor). The mean functional warm ischemic time was 15 min (SD 6 min)‚ and the median duration of NRP was 87 min (interquartile range, 69–101 min). One-year noncensored for death kidney graft survival was 91.3%. The incidence of delayed graft function was 13%. One-year‚ noncensored-for-death liver graft survival was 90.9%. All lung and pancreas recipients had an excellent evolution. One heart recipient died due to a septic shock. Conclusions: This is the largest experience of pediatric cDCD using NRP as graft preservation method. Although our study has several limitations, such as its retrospective nature and the small sample size, its reveals that NRP may increase the utilization of cDCD pediatric organs and offer optimal recipients' outcomes.